Biological and Technical Complications of Splinted or Nonsplinted Dental Implants: A Decision Tree for Selection. Issue 1 (February 2018) - Ravidà, Andrea; Saleh, Muhammad H. A.; Muriel, Miguel Carreño; Maska, Bartosz; Wang, Hom-Lay
Abstract : Purpose: To present an in-depth review on splinting versus nonsplinting the restorations of adjacent dental implants, in addition to discussing biological and technical complications associated with either choice; and to provide the clinician with a decision tree that serves in everyday judgments when it comes to addressing this issue. Materials and Methods: A comprehensive literature review was performed for articles comparing success of splinted versus nonsplinted dental implants. Results: There is no evidence to suggest that implementing either prosthetic design results in higher implant survival. Both designs tend to have their own set of complications, but there is compelling evidence to suggest that splinted restorations generally have less technical complications. Conclusion: Either splinting or nonsplinting are valid options for restoring adjacent implants, but each tend to face different biological and technical complications. Knowing which patients are more likely to face particular complications is strategic to provide patients with successful restorations.